PENGEMBANGAN SISTEM DAN TEKNOLOGI HOME INDUSTRI KANREJAWA BANNANG-BANNANG MELALUI KKN-PPM DI DESA MACCINIBAJI KECAMATAN BATANG KABUPATEN JENEPONTO SULAWESI SELATAN - Siti Suwadah Rimang; Syawaluddin Soadiq (Asian Journal of Innovation and Entrepreneurship, 2015)
The development of society  is always related with poverty which happened to half of society. Nowadays,  poverty is not only Indonesian problem but also  world cases. Indonesia  was identically known with its poverty, however deeply inside this country is willingness to develop and grow up. Therefore, to anticipate the increasing of poor society,   the government through KKN-PPM opened the opportunity widely to help society by cooperation with university that had qualified human resources.One of them  is to help society to improve home industry at target village. It is known that home industry is  main role in nation economic that can hold on crisis time. This additional activity helps them to change their life better  .This research employed such method to visit the society to be trained, create their groups of home industry, conduct training of good products, labeling, business analysis, business development, exhibition, and study comparative to central industry of Makassar. Keyword: home industry, kanrejawa, bannang-bannang, innovation and technology